1990
DOI: 10.1002/mus.880131212
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind trial of mazindol in Duchenne dystrophy

Abstract: There is evidence that growth hormone may be related to the progression of weakness in Duchenne dystrophy. We conducted a 12-month controlled trial of mazindol, a putative growth hormone secretion inhibitor, in 83 boys with Duchenne dystrophy. Muscle strength, contractures, functional ability and pulmonary function were tested at baseline, and 6 and 12 months after treatment with mazindol (3 mg/d) or placebo. The study was designed to have a power of greater than 0.90 to detect a slowing to 25% of the expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Conversely, daily administration of mazindol to five DMD patients for 3 mo yielded no improvement in function but did produce adverse effects such as irritability, sleep disturbances, and elevated heart rate (23). In addition, a subsequent investigation showed that mazindol treatment of 83 boys with DMD for a 12-mo trial did not slow the progression of muscle weakness, but did slow gain in height of the boys (24). More recently, the possibility that exogenous GH could reduce DMD pathology has been revisited, with a particular focus on a potential ameliorative effect on DMD cardiomyopathy (25).…”
mentioning
confidence: 99%
“…Conversely, daily administration of mazindol to five DMD patients for 3 mo yielded no improvement in function but did produce adverse effects such as irritability, sleep disturbances, and elevated heart rate (23). In addition, a subsequent investigation showed that mazindol treatment of 83 boys with DMD for a 12-mo trial did not slow the progression of muscle weakness, but did slow gain in height of the boys (24). More recently, the possibility that exogenous GH could reduce DMD pathology has been revisited, with a particular focus on a potential ameliorative effect on DMD cardiomyopathy (25).…”
mentioning
confidence: 99%
“…As with [47,48], our data suggest that lower IGF-1 circulating levels are more related to a severe than to a benign clinical form of muscular dystrophy.…”
Section: Conclusion and Remarks For Future Studiesmentioning
confidence: 66%
“…As a result, the same authors pointed out that GH inhibitors, such as mazindol, should be used to treat Duchenne muscular dystrophy [45,46]. In contrast, it has been reported that mazindol does not slow the progression of Duchenne dystrophy [47,48] and cause several adverse effects in boys after long term use [48]. The latter studies used IGF-1 determination, which is more accurate than L-DOPA, more stable during the day and does not suffer large secretion oscillations as seen with GH [42,43,26].…”
Section: Conclusion and Remarks For Future Studiesmentioning
confidence: 88%
“…DMD patients are debilitated, having compromised respiratory and cardiac function, and are therefore at increased risk for side effects of the test treatment. 4,5,16 Even with multicenter design, testing therapies in boys with DMD is slow (once enrolled, patients must be followed for 6-18 months). 4,5,16 The RB-mdx treatment test approach carries no patient risk and still yields clinically relevant in vivo data, costs much less, and tests therapies more quickly.…”
Section: Discussionmentioning
confidence: 99%